ARE MARKETS OF CRYPTOCURRENCIES EFFICIENT? : CASE OF ETHEREUM, BITCOIN AND RIPPLE - Kalát, Petr (2017)
This diploma thesis aims to examine three selected cryptocurrencies, Bitcoin, Ethereum and Ripple. First goal of this thesis is to investigate relationship between risk and return, which is accomplished with the use of Capital Asset Pricing Model. Four weeks US Treasury Bill is used as a risk-free proxy and S&P500 index as a market proxy. Estimates reveal strong detachment from influence of the market risk, thus suggesting independency of cryptocurrencies’ returns on market movements. Moreover, negative correlation between Bitcoin and Ripple and the market has been found. These findings suggest suitability of cryptocurrencies as a portfolio addition, which could have essential meaning for investors. Second goal was to examine market efficiency of selected cryptocurrencies. Here weak-form market inefficiency has been found (for Bitcoin and Ethereum), which can imply availability of abnormal profits. Last examined area was possibility of behavioral inefficiencies on the market. Here the weekday anomaly (situation when returns are significantly correlated with some weekday) was not confirmed.